PEDAGOGICAL INSIGHTS INTO ENGLISH SYNTAX AND SENTENCE STRUCTURE (European Journal of Interdisciplinary Research and Development, 2025)
Syntax the study of how words are arranged to form meaningful sentences—is a foundational element of English grammar. For language learners and educators alike, understanding sentence structure in English is essential for developing clear and effective communication skills. This article provides an educational overview of key syntactic concepts, explores types of sentence structures, and introduces practical examples and explanations suited for teaching and learning. It also highlights the role of syntax in language acquisition and classroom instruction.